Review on Effect of Sarshap Taila and Til Taila in Prevention of Atiyog of Karnendriya with Special Reference to Karnanaad - Vivek V. Dhongdi1 , Premkumar Badvaik2 , Shailesh Nagpure3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Lifestyle changes has created lot of hurdles for simple upkramas of Dincharya like Karnapuaran in dailyroutine, leading to commonly occurring disease i.e Karnanad (Tinnitus). It has remained as a formality inHindu festivals like Diwali & Dashera. In some parts of the country to follow rituals like applying Taila onthe body or procedures like Abhyanga and in that case people done karnapuran as well. So, problems relatedto Ear like Karnanad are increasing day by day in atiyog of karnendriya and old aged people in modern era.There are different treatment modalities available for the same, but these are costly. These treatments are notaffordable by low socio economic people. So this review focused with Sarshap Taila and Til Taila to preventatiyog of Karnendriya given in Ayurved.